Pengaruh Kepercayaan,Keamanan dan Kemudahan Terhada Kepuasan Pelanggan Pada J&T Express (Studi Mahasiswa FEB Universitas Islam Malang) - Arinil Haq Musvaida; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to describe trust, security and convenience and customer satisfaction and to determine the effect of trust, security and convenience on customer satisfaction simultaneously or partially. This study uses quantitative methods. This type of research is explanatory research.The population of this study were students of FEB Islamic University of Malang using snowball sampling as many as 85 respondents. The data collection method used a questionnaire. The analytical method used in this study was multiple regression analysis with SPSS 20 for windows.The results of this study indicate that: (1) There is a positive and significant effect of trust on customer satisfaction at J&T Express. (2) There is a positive and significant effect of security on customer satisfaction at J&T Express. (3) There is a positive and significant effect of convenience on customer satisfaction at J&T Express. Keywords: Trust, Security, Ease and Customer Satisfaction